UPAYA MENINGKATKAN HASIL BELAJAR TOLAK PELURU GAYAO’BRIEN MELALUI MODIFIKASI BOLA PLASTIK - Efendi, Muh. Wajedi; Chandra, Dadang Warta; Suriatno, Adi (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
The problem in this research is the low student learning outcomes in grade VII SMPN 4 Central Praya due to inadequate learning facilities. This class action research aims to determine the increase. The method used in this research is descriptive which aims to solve the problems through direct application in the classroom or in the field, subjects used in this study were students of class VII SMPN 4 middle Praya totaling 21 students. This study was conducted in two cycles and each cycle consisting of planning, action, observation / evaluation, and reflection. Instrument od collecting observational data using observation sheets to students through: 1) test: is use to obtain data on learning outcomes shot-put style o’brien, 2) Observation: use to obtain data on the activities of the student activity during learning activities. Data used for analysis of individual mastery learning and classical completeness, which is said to be completed by individual students when obtaining a score of 70 in accordance with the minimum completeness criteria (KKM) and said graduate student in classical completeness if it meets the criteria set forth in the amount of 85%. The result showed that the students’ learning outcome data first cycle of 21 students obtained a total of 14 students or 66.67% which experienced completeness and 7 students or 33.33%, while in the second cycle increased to 18 students or 85.71%, and 3 students or 14.29% did not experience completeness. It proves that in the second cycle learning outcomes to rise and meet the completeness criteria that have been defined in the classical is 85%. Thus it can be said that there is an increasing of learning outcomes through the shot-put style modifications o’brien plastic balls of students in class VII SMPN 4 Central Praya in the academic year 2014/2015.